2010
DOI: 10.1002/dvdy.22372
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the AP‐1 μ1A and μ1B adaptins in zebrafish (Danio rerio)

Abstract: Protein transport between the trans-Golgi network and endosomes is mediated by transport vesicles formed by the adaptor-protein complex AP-1, consisting of the adaptins g1, b1, m1, s1. Mammalia express m1A ubiquitously and isoform m1B in polarized epithelia. Mouse g1 or m1A 'knock out's revealed that AP-1 is indispensable for embryonic development. We isolated m1A and m1B from Danio rerio. Analysis of m1A and m1B expression revealed tissue-specific expression for either one during embryogenesis and in adult ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 39 publications
5
26
0
1
Order By: Relevance
“…Our knowledge about the functions of these complexes and the underlying molecular mechanisms is very limited. Although knockouts of the ubiquitously expressed isoforms are embryonic lethal, knockouts of tissue-specific isoforms are viable, but reveal impaired tissue functions (Glyvuk et al, 2010;Meyer et al, 2000;Takahashi et al, 2011;Zizioli et al, 2010;Zizioli et al, 1999). s1A is ubiquitously expressed at comparable levels in most tissues, whereas its expression in brain is several-fold higher.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our knowledge about the functions of these complexes and the underlying molecular mechanisms is very limited. Although knockouts of the ubiquitously expressed isoforms are embryonic lethal, knockouts of tissue-specific isoforms are viable, but reveal impaired tissue functions (Glyvuk et al, 2010;Meyer et al, 2000;Takahashi et al, 2011;Zizioli et al, 2010;Zizioli et al, 1999). s1A is ubiquitously expressed at comparable levels in most tissues, whereas its expression in brain is several-fold higher.…”
Section: Discussionmentioning
confidence: 99%
“…The dileucine motifs of sortilin and the mannose 6-phosphate (MPR) receptor MPR300 (also known as IGF2R) have been shown to bind to the monomeric clathrin-adaptor protein GGA2 (Nielsen et al, 2001). Like AP-1, GGA2 binds to the TGN and to endosomes, and both are essential for development (Govero et al, 2012;Meyer et al, 2000;Zizioli et al, 2010;Zizioli et al, 1999). Both receptors contain canonical YxxØ-type and dileucine motifs, and a chimera of the MPR luminal domain and the sortilin cytoplasmic tail is able to restore lysosomal enzyme sorting in MPR-deficient cells, indicating that the sortilin and MPR itinerary are largely identical (Nielsen et al, 2001).…”
Section: Sortilin Expression and Adipogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, another favorite model organism, zebrafish, expresses 3 m1 chains, and although zebrafish m1A and m1B have clear homologies to m1A and m1B of higher vertebrates, their expression profile differs. 90,91 For example, whereas m1B expression is missing in the liver of mice, zebrafish expresses m1B in its liver. Furthermore, unlike in mice, m1A is not ubiquitously expressed in zebrafish and missing in its pancreas, liver, and kidneys.…”
Section: Expression Pattern Of Ap-1bmentioning
confidence: 99%
“…Depletion of Drosophila AP-1 or Aftiphilin causes defects in eye development in adult flies Previous studies on the physiological functions of AP-1 revealed that depletion of an AP-1 component causes lethality in mammals, zebrafish, worms and flies (Zizioli et al, 1999;Meyer et al, 2000;Shim et al, 2000;Zizioli et al, 2010;Benhra et al, 2011;Burgess et al, 2005). Because we were interested in how the Golgi clathrin adapter machineries are involved in the development of specific organs of the fly, AP-1 components or other related genes were depleted in the eyes using the GAL4-dependent knockdown system (Dietzl et al, 2007), and phenotypic analysis of the knockdown flies was carried out.…”
Section: Resultsmentioning
confidence: 99%